Supporting the diagnosis of infantile colic by a point of care measurement of fecal calprotectin - Sommermeyer, Henning; Bernatek, Malgorzata; Pszczola, Marcin; Krauss, Hanna; Piatek, Jacek (Frontiers in Pediatrics, 2022)
Background Infantile colic (IC) is a condition characterized by extensive crying which affects about 20% of all infants during their first months of life. Most pediatricians diagnose IC only based on their clinical experience. Aim Investigating if a measurement of fecal calprotectin can support the diagnosis of IC. Methods The crying behavior of newborns was assessed using the Wessel's criteria. Fecal calprotectin levels were measured in non-colicky and colicky babies using a standard test that can be used at the time and place of patient care (point of care (PoC) measurement). Results Colicky babies were found to have significantly elevated fecal calprotectin levels. Calprotectin levels were not influenced by gender, type of feeding, gestation age or birth weight. However, significantly elevated fecal calprotectin levels were found in cesarean section born babies. Fecal calprotectin ≥100 μg/g correlated with a colicky status of an infant while those <100 μg/g indicated a non-colicky status the error margin was 11.2 and 13.2%, respectively. Combining data of fecal calprotectin with information about the type of delivery made it possible to determine the colicky status in vaginally-born infants with fecal calprotectin ≥100 μg/g with an accuracy of 97.8%. As elevated fecal calprotectin levels in cesarean-born infants can be caused by IC, but also by the disturbed gut microbiota commonly found in these babies, the accuracy of diagnosing the colicky status of a cesarean-born infant with calprotectin levels ≥100 μg/g was less accurate (accuracy rate of 76.5%). Conclusion Data from the study suggest that measuring fecal calprotectin should be considered by pediatricians to support the diagnosis of IC. The study was registered at ClinicalTrials.gov under NCT04666324.